O fazer do intérprete educacional: práticas, estratégias e criações - Santos, Lara Ferreira dos (Universidade Federal de São Carlos, 2014)
This research aimed to analyze and discuss the work of the Educational Interpreter (IE), which is a recent professional in our country, and the currently researches on their performance in the classroom are incipient in order to better understanding of the practices, strategies and creations in the process of translation and language interpretation to/from Brazilian Sign Language. This thesis aimed to uncover what is behind the work of interpretation from one language to another, what factors influence either positively or negative, the performance of the IE, considering the authorship, the another s discourse, the polysemy of the language involved, and, specially, the creation or transcreation. This research is based on Bakhtinian theoretical frameworks (2009, 2010), because we believe that the language is a concrete activity and is related to life and its character is dialogic. It is not possible the understanding of the IE performance unless with unique acts, which are possible in a specific time and space with real interlocutors that enunciate and expect answers. In order to embrace the entire events surrounding the IE s work (even aware of the impossibility of it), this research were conducted as a qualitative investigation influenced by microethnographic approach. The data collection was done over the second semester of 2011 and it s been observed four IE during their work in four different classrooms, whose classes were taught by three teachers from the final years of elementary school in an Inclusive Educational Program school and bilingual teaching for deaf. In order to tape-record the natural and quotidian situations of the translation process conducted by the IEs we followed the classes and everything that happened during the classes. From the data collected it has selected nine episodes to be analyzed, which were divided into three main axes, titled: the collective construction of knowledge in a context of dialogue-education ; narrative supported by imagetic representations . The analysis and reflections on the IE s performance led us to the construction of a thesis that the work of Educational Interpreter is not restricted to the utterances translation and interpretations. Its daily practices go beyond this aspect. The Educational Interpreter is co-author of the discourses delivered by teachers in classroom. We assume that the classroom context is so complex that the teachers utterances would be untranslated (as some on the translation field authors have said), not because of linguistics issues or by their way of presentation, but because of lots of elements involved. Finally, we list some notes that were relevants to the Educational Interpreters training in order to contribute to these professionals from new perspectives.
Keywords: Intérprete educacional; Língua brasileira de sinais; Tradução e interpretação; Surdez; Educational interpreter; Brazilian sign language; Translation and language interpretation to/from libras; Deafness; Special education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL